Strengthening the Quality of Education through Curriculum Innovation Management in Private Islamic Senior High Schools - Nurotun Mumtahanah; Ahmad Hanif Fahruddin; Muhammad Aziz; Leni Duwi Noviana (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2026)
This article explains how curriculum innovation is managed to improve educational quality in madrasas, focusing specifically on MA Al-Rosyid Bojonegoro and MA Assalam Tuban. The research uses a field study design with a qualitative–descriptive method and a multiple case study approach. Data were gathered through interviews, observations, and document analysis, and subsequently analyzed within and across cases. The findings show that the planning of curriculum innovation in both madrasas has been structured and carried out effectively to enhance educational quality. This planning includes: (1) the delivery of information related to the conditions and urgency of innovation by the Madrasah principal in a structured manner and in accordance with regulations; (2) active participation of teachers, education staff, committees, and parents; (3) determination of curriculum implementation through annual and semester meetings approved by all related parties; (4) implementation of continuous evaluation through meetings, observations, and routine monthly meetings between the Madrasah principal and the curriculum head, as well as semester meetings with teachers; and (5) holding meetings with parents and the committee at the end of the semester. Theoretically, this research contributes to strengthening the discourse on the quality management of Islamic education in the context of curriculum innovation. At the same time, practically, it offers strategic recommendations for curriculum management in private madrasas in rural areas.